Pacto nacional pelo fortalecimento do ensino médio e a integração das tecnologias de informação e comunicação - Quaresma, Cíndia Rosa Toniazzo (2015)
This study investigated the integration of the information and communication technologies TIC on high school curriculum, having as context the formation process of National Pact for High School‟s Strengthening (PNFEM). In order to contribute for the school practices innovation, were made teachers‟ technologies formation meetings to offer theoretical and practical subsidies for the integration of TIC on curriculum. In this context, the research conception was the action investigation and the dados were collected with observation sheets; research diary and questionnaire. Then, for the analyses were used the following categories: formation of PNFEM; integration of TIC at the pedagogical practices; innovative pedagogical strategies, tools, resources and/or network platforms. As results are pointed out: 1) the school practices innovation, from the integration of TIC; 2) authoring process of the teachers involved, through the class production for Teachers‟ Portal (MEC). The continuing education in the school environment as a PNFEM‟s pillar, was determinant to reach the results. As conclusions, stands out that the mediated proposals construction by TIC made emerge other ways of production beyond the classroom; and that some factors limit the integration of TIC, as the lack of a quality structure to a network access, mainly in classroom and the absence of a technical and pedagogical guideline to undertake pedagogical proposals which support the implementation of these.